Physical fitness has no influence on elite tennis player's ranking? - Ruzic, L.; Matkovic, B.; Vucetic, V.; Barbaros-Tudor, P.; Canaki, M.; Cigrovski, V. (Science and Profession - Challenge for the Future, 2005)
The aim of the study was to determine the eventual influence of standard testing protocols used in tennis on current ranking of elite tennis players as well as on maximal serve velocity. Twenty Croatian national and international male elite tennis players were ranked according to the ATP and National ranking order at the end of the season and underwent a laboratory exercise testing procedure, which encompassed measurements of morphological, motor and functional characteristics and abilities. The insight to the eventual influence of the measured abilities on overall ranking was obtained by multiple regression analysis. Neither the model nor the single variable proved to be significant in predicting the ranking of the elite tennis players or maximal ball velocity during serve. Very good results in aerobic capacity, strength and coordination test probably contributed to the lack of significance of the proposed model on rank because all subjects were well prepared from physical fitness point of view. Also, the sample comprised only top-level athletes among whom the ranking is probably influenced by slight differences in tennis technique and, of course, psychological factors.